Work of Terrence Malick : time-based ecocinema - Blasi, Gabriella (Amsterdam University Press, 2019)
The Work of Terrence Malick: Time-Based Ecocinema develops a timely ecocinema approach to film analysis illuminated by Benjamin's notion of the turn of time. Current work on Malick's films emphasizes the spatial dynamics of his cinema, particularly as it pertains, from within a phenomenological framework, to the viewer's experience of films. This book redirects scholarly attention to the way Malick's directorial work shapes time and duration, laying new groundwork for the analysis of how films unsettle nature-culture binaries in modernity. The study performs this intervention through a rigorous engagement with Walter Benjamin's work on time, violence and technologies and the emergent figural approach to aesthetics in film studies. Each of these methods has important precedents in film studies and other fields. The combination of methods performed in this book contributes to understanding the relevance of a time-based approach to Malick's films and the practical implications of a time-based relation to history in contemporary ecocinema discourses.
Keywords: Malick, Terrence, -- 1943- -- Criticism and interpretation.; Malick, Terrence, -- 1943-; Motion picture producers and directors -- United States.; Environmentalism in motion pictures.; Ecology in motion pictures.; Producteurs et réalisateurs de cinéma -- États-Unis.; Environnementalisme au cinéma.; Film theory and criticism.; Individual film directors, film-makers.; ART / Criticism.; Ecology in motion pictures; Environmentalism in motion pictures; Motion picture producers and directors; United States; Criticism, interpretation, etc.